Nonlinear association between lung needle path CT attenuation values and postprocedural immediate pneumothorax following computed tomography-guided lung biopsy: a retrospective cohort study - Shao-quan Zhou; Fang Luo; Xiong Ran; Jian Yang; Fu-rong Lv; Kang Li (BMC Pulmonary Medicine)
Abstract Background Pneumothorax is a potential complication following computed tomography-guided lung biopsy (CT-LB). However, the relationship between the lung needle path CT attenuation values and risk of post-procedural immediate pneumothorax remains unclear. The study aims to investigate this relationship. Methods The present single-center retrospective cohort study analyzed the data obtained from 453 patients who underwent CT-LB from 2019 to 2022. The relationship between the lung needle path CT attenuation values and post-procedural immediate pneumothorax was assessed using restricted cubic splines, which were adjusted for potential confounders, and validated using linear and nonlinear binomial logistic models. Results A total of 453 patients (mean age: 60.2 ± 12.0 years old, 217 male patients) were evaluated. The incidence of post-procedural immediate pneumothorax was 41.06% (186/453). The median needle path CT attenuation was − 831 Hounsfield units (Hu). The linear models indicated an unstable association between lung needle path CT attenuation and post-procedural immediate pneumothorax (odds ratio: 0.99, 95% confidence interval: 0.99-1.00). The nonlinear analysis identified an inflection point at a CT attenuation value of -805 Hu. A stronger negative link was identified for needle path CT attenuation values below − 805 Hu (odds ratio: 0.99, 95% confidence interval: 0.98–0.99) between the needle path CT attenuation value and pneumothorax, while no statistically significant association was identified between these when the CT attenuation value was above − 805 Hu. Conclusion There is a nonlinear association between the lung needle path CT attenuation values and risk of post-procedural immediate pneumothorax. For CT attenuation values below − 805 Hu, increasing the needle path CT attenuation values might reduce the risk of pneumothorax.